Microbiome resilience of three-toed box turtles (Terrapene carolina triunguis) in response to rising temperatures - Guan, Jimmy; Ramírez, Gustavo A.; Eng, Curtis; Oakley, Brian (Frontiers in Veterinary Science, 2024)
The gastrointestinal (GI) microbiome of chelonians (testudines) plays an important role in their metabolism, nutrition, and overall health but the GI microbiome of three-toed box turtles (Terrapene carolina triunguis) has yet to be characterized. How the GI microbiome responds to rapidly rising environmental temperatures has also not been studied extensively in ectotherms, specifically chelonians. In this study, twenty (20) T.c.triunguis were split into control and experimental groups. The experimental group experienced 4.5°C increases every two weeks while the control group stayed at a constant ambient temperature (24°C) through the entirety of the experiment. Before each temperature increase, all turtles had cloacal swab samples taken. These samples underwent DNA extraction followed by 16S rRNA gene sequencing and microbial community analyses. Differences in diversity at the community level in the controls compared to the experimental groups were not statistically significant, indicating microbiome resilience to rapid temperature changes in T.c.triunguis, although some differentially abundant lineages were identified. Interestingly, an amplicon sequence variant belonging to the Erysipelothrix spp. was exclusively enriched in the highest temperature group relative to controls. Overall, our work suggests that there may be an innate robustness to rapid temperature swings in the microbiome of T.c.triunguis which are native to temperate North America. Despite this resilience, Erysipelothrix spp. was enriched at the highest temperature. Phylogenetic analysis of this amplicon variant showed that it is a close relative of Erysipelothrix rhusiopathiae, a pathogen of zoonotic importance associated with both wildlife and livestock.